129k views
4 votes
Prove that: (secA-cosec A) (1+cot A +tan A) =( sec^2A/cosecA)-(Cosec^2A/secA)


User Mandaleeka
by
4.8k points

1 Answer

5 votes

Explanation:


(\sec A - \csc A)(1 + \cot A + \tan A)


=(\sec A - \csc A)\left(1 + (\cos A)/(\sin A) + (\sin A)/(\cos A) \right)


=(\sec A - \csc A)\left(1 + (\cos^2 A + \sin^2 A)/(\sin A\cos A) \right)


=(\sec A - \csc A)\left((1 + \sin A \cos A)/(\sin A \cos A) \right)


=\left(((1)/(\cos A) - (1)/(\sin A)+\sin A - \cos A)/(\sin A\cos A)\right)


=(\sin A - \sin A \cos^2A - \cos A + \cos A\sin^2A)/((\sin A\cos A)^2)


=(\sin A(1 - \cos^2A) - \cos A (1 - \sin^2 A))/((\sin A\cos A)^2)


=(\sin^3A - \cos^3A)/(\sin^2A\cos^2A)


=(\sin A)/(\cos^2A) - (\cos A)/(\sin^2A)


=\left((1)/(\cos A)\right)\left((\sin A)/(1)\right) - \left((1)/(\sin^2A)\right) \left((\cos A)/(1)\right)


=\sec^2A\csc A - \csc^2A\sec A

User Thesane
by
6.0k points